Epstein–Barr virus, cytomegalovirus and BK polyomavirus burden in juvenile systemic lupus erythematosus: correlation with clinical and laboratory indices of disease activity. (September 2020) - Aygun, Deniz; Kuskucu, Mert Ahmet; Sahin, Sezgin; Adrovic, Amra; Barut, Kenan; Yıldız, Mehmet; Sharifova, Sabina; Midilli, Kenan; Cokugras, Haluk; Camcıoglu, Yıldız; Kasapcopur, Ozgur
Objectives: Clinical and laboratory investigations have revealed that Epstein–Barr virus (EBV) is involved in altered immunological response of systemic lupus erythematosus (SLE). Higher seroprevalence rates of anti-EBV antibodies and increased viral load are demonstrated in adult SLE patients. The prevalence of BK polyomavirus (BKV) reactivation is also suggested to be higher in SLE. Herein, we aimed to evaluate the immune response of children with SLE to EBV antigens in addition to EBV and BKV DNA. We also tried to evaluate whether these serological results differ from another connective tissue disease – juvenile systemic sclerosis (jSS) – and healthy individuals. Methods: Serum levels of EBV early antigen diffuse (EA-D) IgG, EBV nuclear antigen-1 IgG, EBV viral capsid antigen (VCA), cytomegalovirus (CMV) IgG, EBV DNA, CMV DNA and urinary BKV DNA were evaluated in healthy controls and in patients with a diagnosis of juvenile SLE (jSLE) and jSS. Results: A total of 70 jSLE patients, 14 jSS patients and 44 sex-matched healthy individuals were involved in the study. EBV VCA was positive in 84.2% of jSLE patients, 85.7% of jSS patients and 36.3% of healthy controls. EBV EA-D IgG positivity was significantly higher in jSLE patients compared to jSS patients and healthy controls (20% vs. 7.1% and 0%, p  = 0.005). EBV VCA positivity was associated with malar rash and immunological disorder, but there was no statistical significance in other antibody positivity in terms of clinical and haemogram findings and autoantibody positivity. CMV DNA positivity was present in only 2.8% of jSLE patients. None of the jSS patients or the healthy controls had CMV DNA positivity. EBV DNA and BKV DNA were also negative in all three groups. Conclusion: The results of our study assume a relationship between SLE and EBV, but we could not demonstrate an association between CMV and BKV. The negative DNA results in contrast to serological positivity can be interpreted as an altered and impaired immune system and increased viral susceptibility. These results suggest that EBV contributes to disease continuity, even if it does not directly cause development.